Isotropic Remeshing with Fast and Exact Computation of Restricted Voronoi Diagram - Yan, Dong-Ming; Lévy, Bruno; Liu, Yang; Sun, Feng; Wang, Wenping (Eurographics Symposium on Geometry Processing 2009, 2009)
We propose a new isotropic remeshing method, based on Centroidal Voronoi Tessellation (CVT). Constructing CVT requires to repeatedly compute Restricted Voronoi Diagram (RVD), defined as the intersection between a 3D Voronoi diagram and an input mesh surface. Existing methods use some approximations of RVD. In this paper, we introduce an efficient algorithm that computes RVD exactly and robustly. As a consequence, we achieve better remeshing quality than approximation-based approaches, without sacrificing efficiency. Our method for RVD computation uses a simple procedure and a kd-tree to quickly identify and compute the intersection of each triangle face with its incident Voronoi cells. Its time complexity is O(mlogn), where n is the number of seed points and m is the number of triangles of the input mesh. Fast convergence of CVT is achieved using a quasi-Newton method, which proved much faster than Lloyd’s iteration. Examples are presented to demonstrate the better quality of remeshing results with our method than with the state-of-art approaches.